2016
DOI: 10.1016/j.metabol.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D in bariatric surgery: A systematic review of observational studies

Abstract: Background Obesity is a public health problem that carries global and substantial social and economic burden. Relative to non-surgical interventions, bariatric surgery has the most substantial and lasting impact on weight loss. However, it leads to a number of nutritional deficiencies requiring long term supplementation. Objectives The aims of this paper are to review 25-hydroxyvitamin D [25(OH)D] status pre and post - bariatric surgery, describe the dose response of vitamin D supplementation, and assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 111 publications
4
77
1
6
Order By: Relevance
“…In a study from Sweden, 65% of patients had serum 25(OH) vitamin D levels less than 20 ng/dL and 69% had elevated PTH levels after a median time of 11±2.8 years postsurgery (4). Similar results have been found in other studies despite replacement of vitamin D and calcium (12). As a result lifelong calcium and vitamin D supplements are mandatory for these patients.…”
Section: Discussionsupporting
confidence: 90%
“…In a study from Sweden, 65% of patients had serum 25(OH) vitamin D levels less than 20 ng/dL and 69% had elevated PTH levels after a median time of 11±2.8 years postsurgery (4). Similar results have been found in other studies despite replacement of vitamin D and calcium (12). As a result lifelong calcium and vitamin D supplements are mandatory for these patients.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, in studies of obese individuals preparing for bariatric surgery, mean preoperative 25(OH)D levels are consistently below 30 ng/mL and often below 20 ng/mL [72]. After RYGB, prevalence of vitamin D insufficiency or deficiency remains high [65,72], although reported prevalence varies substantially due to heterogeneity in approach to postoperative supplementation.…”
Section: Vitamin D and Bariatric Surgerymentioning
confidence: 99%
“…After RYGB, prevalence of vitamin D insufficiency or deficiency remains high [65,72], although reported prevalence varies substantially due to heterogeneity in approach to postoperative supplementation. Even at a given supplement dose, response to supplementation is highly variable after RYGB [65,72], with some individuals achieving 25(OH)D levels above 30 ng/mL on just 400 IU daily while others require 50,000 IU daily or more.…”
Section: Vitamin D and Bariatric Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, hypovitaminosis D remains a major problem, not only pre-operatively but also post operatively, regardless of the type of the procedure and the supplementation dose [5, 6]. In a recent systematic review of 51 observational studies assessing 25(OH)D status in obese patients undergoing bariatric surgery (follow up range: 3 months to 11 years post-operatively), mean 25-hydroxyvitamin D (25(OH)D) level was less than 30 ng/ml, before and after bariatric surgery, despite various vitamin D supplementation regimens [7]. Furthermore, 25(OH)D level was less than 20 ng/ml in half of the studies that were identified [7].…”
Section: Introductionmentioning
confidence: 99%